Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2174/157340206778132536
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hypertension and Atherosclerosis: From a Viewpoint of the Most Potent Vasoconstrictor Human Urotensin II

Abstract: Human urotensin II (U-II), the most potent vasoconstrictor peptide identified to date, and its receptor (UT) are involved in etiology of hypertension. In hypertensive patients, U-II induces vasoconstriction in forearm brachial artery infusion studies. Recent studies demonstrated elevated plasma U-II concentrations in patients with hypertension, diabetes mellitus, atherosclerosis, and coronary artery disease. U-II is expressed in endothelial cells, macrophages, macrophagederived foam cells, and myointimal and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Hypertension is regarded as a promotive and risk factor of atherosclerosis [1]. Several lines of evidence have shown that endothelial injury, an initial step of atherosclerosis, is caused by hypertension-induced pressure overload, stretch, or shear stress on the artery wall [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is regarded as a promotive and risk factor of atherosclerosis [1]. Several lines of evidence have shown that endothelial injury, an initial step of atherosclerosis, is caused by hypertension-induced pressure overload, stretch, or shear stress on the artery wall [2].…”
Section: Introductionmentioning
confidence: 99%